FPM PADA KELUARGA EKSPONENSIAL BENTUK KONONIK - Puspita, Mrs Entit (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2002)
We can determine the distribution of the random variable by considering its moment generating function (MGF). Unfortunately there are some distribution which have no MGF. This kind of the problem cannât occur on an exponential family, because the comunic form of the family always can be determined its MGF.Kata kunci : Bentuk kanonik, keluarga eksponensial, fungsi pembangkitan momen.